Optimum Stage of Growth for Harvesting the Leaves of Indian Belladonna Cultivated in the Chakrata Hills - Sethi, H.; Sharma, B. K.; Beri, R. M. (Indian Forester, 1965)
Experiments conducted in the Chakrata Hills have shown that the alkaloidal content of the leaves of Indian Belladonna (Atropa acuminala Royle ex Lindl.) is highest when the flower buds are in the primordial stage and the amount of alkaloids decreases as the development of the flower progresses. The optimum stage of growth for harvesting the leaf drug appears to be the "Advanced Flower-bud Stage".